Show and Tell Learning Method Based on the Discovery Learning Model: Creativity and Learning Outcomes at Primary School - Nur, Zahra; Mulyadi, Mulyadi; Nurdiansyah, Erwin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Conventional and boring learning paradigms typically lead to low creativity and learning outcomes in Pancasila and Citizenship Education. Researchers at Primary School 126 Inpres Kariango, Maros Regency, found a new way to attract kids interested in civics. This study examines how the Discovery Learning-based Show and Tell learning technique influences fifth-grade students' creativity and learning at Primary School 126 Inpres Kariango. This research is an experimental quantitative study. The study included 30 fifth graders. Pretests and posttests measured learning outcomes, and observation sheets measured student inventiveness. To assess intervention efficacy, descriptive and inferential statistics were used, including normality, homogeneity, and t-tests. The findings found considerable improvements in all areas: (1) Teacher instruction improved from